Surgical and prosthetic treatment of a patient with Wegener’s granulomatosis - Zelik-Święch, Dominika; Święch, Karol; Stopa, Zygmunt; Adamiec, Marcin; Gawlak, Dominika (Journal of Stomatology, 2017)
Wegener's granulomatosis is an uncommon systemic disease that belongs to the group of necrotizing granulomatous vasculitides. The disease generally involves the upper and lower respiratory tract and kidneys. In the oral cavity it is manifested by hyperplastic granular gingivitis called “strawberry gingivitis”. This article presents a female patient who suffered from Wegener’s granulomatosis with indications for surgical and prosthetic treatment. At the time of the first visit, the clinical examination revealed missing teeth replaced with fixed prostheses, teeth denudation and mobility. After analyzing the clinical status and orthopantomograph, it was decided to extract all maxillary teeth and fabricate immediate complete upper denture. Follow-up appointments showed prolonged healing with significant and uneven loss of bone tissue. Despite this the patient adapted quite well to the prosthesis. After three weeks, Mollosil (Detax, Germany) soft relining material was applied, which was then replaced with acrylic one. After stabilization of the prosthetic surface, construction of a new upper denture is planned.